The little white schoolhouse - Hartford, Ellis Ford, 1905- (Kentucky Bicentennial bookshelf., 1977)
Few institutions have been held in such fond regard and recalled in such nostalgic terms as the little red schoolhouse. It ranks with the old oaken bucket, the little brown church in the vale, and the pictures of the old home place that millions of people have carried in that ""inward eye"" mentioned by Wordsworth on that long-past spring day. But the Kentucky common schoolhouses were not painted red as were those of New England; they were mostly white, if not of unpainted log construction.It was not the simple little boxlike schoolhouse itself that earned all that fond affection. What happened.